Misconception and Legal Problems of Authority to Perform Medical Actions in Nursing Administrative Law - P. Sibuea, Hotma; Seno Wijanarko, Dwi; Johardi Wirogioto, Ali; Lorenly Nainggolan, Indra; Siagian, Katrina (Riviera Publishing, 2023)
According to Article 29 paragraph (1) of Law Number 38 of 2014, nurses have several duties, namely as providers of nursing care, counselors and client counselors, managers of nursing services, nursing researchers, and task performers based on delegated authority and/or tasks in specific limited circumstances. One of the nurse's tasks that receives focused attention is